STRATEGY ANALYSIS OF THE TRADITIONAL MARKET TRADERS AT THE TIME OF THE COVID-19 PANDEMIC - Khaeruman, Khaeruman; Suflani, Suflani; Jawahir, Masmanto Moh (Yayasan Education and Social Center, 2022)
This research uses qualitative research methods. The type of research is field research with a descriptive approach, the Data collection techniques through observation, interviews and documentation. Data analysis techniques are analyzed before the field and data analysis in the area with the stages of reducing data, presenting data and drawing conclusions. The results have shown that there are three types of survival strategies that can carry out, namely: 1) active strategies, improving the quality of goods and services, the presence of family members who help work, and increasing hours of work, 2) passive strategies, namely by reducing stock items, by reducing the number of employees, 3) network strategy, by building good relationships with buyers, leaving goods in the nearest stands, and doing online business online